Autosomal dominant tubulointerstitial kidney disease: more than just HNF1β - Bleyer, Anthony J.; Wolf, Matthias T.; Kidd, Kendrah O.; Zivna, Martina; Kmoch, Stanislav (Pediatric nephrology (Berlin, West), 2022)
Autosomal dominant tubulointerstitial kidney disease (ADTKD) refers to a group of disorders with a bland urinary sediment, slowly progressive chronic kidney disease (CKD), and autosomal dominant inheritance. Due to advances in genetic diagnosis, ADTKD is becoming increasingly recognized as a cause of CKD in both children and adults. ADTKD- REN presents in childhood with mild hypotension, CKD, hyperkalemia, acidosis, and anemia. ADTKD- UMOD is associated with gout and CKD that may present in adolescence and slowly progresses to kidney failure. HNF1β mutations often present in childhood with anatomic abnormalities such as multicystic or dysplastic kidneys, as well as CKD and a number of other extra-kidney manifestations. ADTKD- MUC1 is less common in childhood, and progressive CKD is its sole clinical manifestation, usually beginning in the late teenage years. This review describes the pathophysiology, genetics, clinical characteristics, diagnosis, and treatment of the different forms of ADTKD, with an emphasis on diagnosis. We also present data on kidney function in children with ADTKD from the Wake Forest Rare Inherited Kidney Disease Registry.